Raf Kinase Inhibitor Protein Expression and Prognostic Value in Soft Tissue Sarcomas - Martinho, Olga; Campos, Marcelo [UNESP]; Ribeiro, Guilherme; Penna, Valter; Curcelli, Emílio C. [UNESP]; Olivieri, Marcus V.; Morini, Sandra; Scapulatempo, Cristovam; Abrahaõ-Machado, Lucas F.; Reis, Rui M. (Karger Publishers, 2016)
Objective: Soft tissue sarcomas (STSs) are heterogeneous tumors displaying multiple and complex molecular abnormalities with no specific pattern. Despite current therapeutic advances, the patients with STS still have a poor outcome, which makes it necessary to find out new prognostic markers. The Raf kinase inhibitory protein (RKIP) has been associated with prognosis in several human neoplasms; however, its role in STS is unknown. Methods: In the present study RKIP expression was assessed by immunohistochemistry in a series of 87 STSs, and its expression profile was associated with the patients' pathological parameters. Results: We found that RKIP is expressed in the cytoplasm of the great majority of cases, and absent in only approximately 18% of cases (16/87). Importantly, we observed that loss of RKIP expression was associated with poor outcome, constituting an independent prognostic marker. Conclusion: This is the first study assessing RKIP expression levels in STS. We showed that loss of RKIP expression is present in a small subset of cases; however, its absence was associated with poor survival and may be a potential marker for STS prognosis.
Keywords: Prognosis; Raf kinase inhibitor protein; Sarcomas